Identifying lifelong factors that impact brain health and functional outcomes in adults with childhood-onset type 1 diabetes: the cognition and longitudinal assessments of risk factors over 30 years (CLARiFY) – diabetes complications study protocol - Velandai K Srikanth; Eva L Feldman; Chris Moran; Lili Zhao; Amy Brown; Richard Beare; Elisabeth A Northam; Emily J Koubek; Stacey A Sakowski; Taya Collyer; Chris L. Adamson; Fergus J. Cameron (BMJ Open)
Introduction Type 1 diabetes (T1D) is associated with changes in brain structure, cognition, mental health, and functional outcomes. While these changes have been linked to dysregulated glycaemic control, findings are inconsistent, and their long-term impact remains unclear. Most evidence comes from cross-sectional or short-term longitudinal studies, limiting insights into causal associations. To address this, we aim to study individuals with T1D approximately 30 years after onset to assess how early dysglycaemic insults during neurodevelopment influence cognitive and functional outcomes in mid-adulthood.Methods and analysis This protocol paper outlines an observational, case/control, cross-sectional/longitudinal and descriptive study that follows up the original Royal Children’s Hospital (RCH) Diabetes Cohort Study. The initial study recruited children in Australia diagnosed with T1D between 1990 and 1992, conducting five waves of data collection. We now introduce the Cognition and Longitudinal Assessments of Risk Factors over 30 Years (CLARiFY) Diabetes Complications Study to assess brain, cognition and functional outcomes in mid-adulthood, approximately 30 years post-T1D onset. Both T1D participants from the original cohort and healthy controls will participate in semistructured interviews, neuroimaging and cognitive testing. T1D participants will also undergo complications screening. Data from this study and previous waves will be used to (Aim 1) explore cross-sectional and longitudinal impacts of T1D on brain health over 30 years. Linear regression will analyse cross-sectional outcomes, and multivariate analysis will assess cognitive variables jointly. Longitudinal outcomes will be examined using linear mixed-effects regression for IQ patterns, with secondary outcomes analysed via generalised linear models. Additionally, linear mixed-effects regression (Aim 2) will identify T1D-related metabolic factors affecting brain outcomes, with covariate selection informed by the construction of directed acyclic graphs (DAGs).Ethics and dissemination The study was approved by the Royal Children’s Hospital Human Research Ethics Committee (HREC 35 240F and 2019.065). The research findings will be disseminated through peer-reviewed publications, conference presentations, and print and social media. Participants will receive a summary of the study findings on its completion.